PENGETAHUAN DAN PENGGUNAAN TUMBUHAN KOWALA (AREN) PADA MASYARAKAT MUNA DI KECAMATAN WATOPUTE KABUPATEN MUNA - Basri, La Ode Ali (Universitas Halu Oleo, 2020)
The purpose of this study is to know and analyze the traditional Muna knowledge in Watopute District regarding the perception, management, and utilization of kowala (sugar palm/) plants. Data collection is carried out through in-depth interviews, engaged observations, and focused discussions. Data analysis is performed through data reduction, data presentation, and drawing conclusions. The results showed that the community perceive sugar palm plants as special plants because all parts of the plant, from the roots to the tops, are useful for humans and are useful in creating ecological balance. The Watopute community makes the sugar palm plant as a teacher of life institutionalized in a value system through the traditional expression